Middle East Respiratory Syndrome Coronavirus in Dromedaries in Ethiopia Is Antigenically Different From the Middle East Isolate EMC - Shirato, Kazuya; Melaku, Simenew Keskes; Kawachi, Kengo; Nao, Naganori; Iwata-Yoshikawa, Naoko; Kawase, Miyuki; Kamitani, Wataru; Matsuyama, Shutoku; Tessema, Tesfaye Sisay; Sentsui, Hiroshi (Frontiers in Microbiology, 2019)
Middle East respiratory syndrome (MERS) is an emerging respiratory disease caused by the MERS coronavirus (MERS-CoV). MERS has been endemic to Saudi Arabia since 2012. The reservoir of MERS-CoV is the dromedary camel, suggesting that MERS is primarily a zoonotic disease. MERS-CoV is common in dromedaries throughout the Middle East, North Africa, and East Africa as evidenced by neutralizing antibodies against MERS-CoV; however, human cases have remained limited to the Middle East. To better understand the cause of this difference, the virological properties of African camel MERS-CoV were analyzed based on the spike (S) protein in Ethiopia. Nasal swabs were collected from 258 young dromedaries (≤ 2 years old) in the Afar region of Ethiopia, of which 39 were positive for MERS-CoV, as confirmed by genetic tests. All positive tests were exclusive to the Amibara woreda region. Using next-generation sequencing, two full-length genomes of Amibara isolates were successfully decoded; both isolates belonged to the C2 clade based on phylogenetic analysis of full-length and S protein sequences. Recombinant EMC isolates of MERS-CoV, in which the S protein is replaced with those of Amibara isolates, were then generated to test the roles of these proteins in viral properties. Amibara S recombinants replicated more slowly in cultured cells than in EMC S recombinants. In neutralizing assays, Amibara S recombinants were neutralized by lower concentrations of sera from both Ethiopian dromedaries and EMC isolate (wild-type)-immunized mouse sera, relative to the EMC S recombinants, indicating that viruses coated in the Amibara S protein were easier to neutralize than the EMC S protein. Neutralization experiments performed using S1/S2 chimeric recombinants of the EMC and Amibara S proteins showed that the neutralization profile was dependent on the S1 region of the S protein. These results suggest that the slower viral replication and the ease of neutralization seen in the Ethiopian MERS-CoV are due to strain-specific differences in the S protein and may account for the absence of human MERS-CoV cases in Ethiopia.